Pengaruh Implementasi Game Based Learning Terhadap Prestasi Belajar Santri Kelas 2 TMI Al-Amien Prenduan Sumenep Madura Tahun 2023 - Goffar, Fahrian; Wahid, Musleh (UNIVERSITAS SERAMBI MEKKAH, 2025)
As time progresses and modernization takes place in our country, especially in Indonesia, we should focus more on developing education rather than remaining stagnant in just one aspect. However, in doing so, we must not lose the identity of an institution. Game-based learning is a game deliberately created for educational purposes as a supporting media for learning, as it is considered more engaging compared to conventional teaching methods. Therefore, game-based learning becomes important because it can serve as an educational medium that makes children more interested in learning and helps them understand lessons better, compared to the conventional and often monotonous teaching methods that tend to make students bored during the learning process.The researcher intends to use a quantitative approach, which involves using numbers or statistics. This research yielded some less positive results, where the relationship between the implementation of game-based learning and academic achievement was either absent or not significant. Therefore, this research indicates that the implementation of game-based learning does not have a significant impact on improving the academic achievement of second-year students at TMI Al-Amien Prenduan, with the calculated t-value being smaller than the t-table value, meaning that the alternative hypothesis (Ha) is rejected, and the null hypothesis (Ho) is accepted. Based on these values, it can be concluded that the implementation of game-based learning does not significantly affect the academic achievement of second-year students at TMI Al-Amien Prenduan.